-7+4x < -4x+5

-7 + 4x < -4x + 5; 4x + 4x < 5 + 7; 8x < 12; x < 12/8; x < 3/2

Question

Asked 5/1/2014 11:29:19 AM

Updated 7/10/2018 8:33:51 AM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Rating

8

-7 + 4x < -4x + 5;

4x + 4x < 5 + 7;

8x < 12;

x < 12/8;

x < 3/2

4x + 4x < 5 + 7;

8x < 12;

x < 12/8;

x < 3/2

Added 7/10/2018 8:33:51 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/10/2018 10:37:16 AM]

-38 - (-51)

Question

Updated 5/3/2014 5:46:44 PM

1 Answer/Comment

-38 - (-51);

-38 + 51

= 13

-38 + 51

= 13

Added 5/3/2014 5:46:44 PM

This answer has been confirmed as correct and helpful.

17.87+(-2.94)+0.81

Question

Updated 5/3/2014 9:33:05 AM

1 Answer/Comment

17.87+(-2.94)+0.81

= 17.87-2.94+0.81

= 15.74

= 17.87-2.94+0.81

= 15.74

Added 5/3/2014 9:33:05 AM

This answer has been confirmed as correct and helpful.

2[5a - 4a(2a +4b)+8a to the second power]

Question

Updated 6/6/2014 2:28:22 AM

2 Answers/Comments

2[5a - 4a(2a +4b) + 8a^2]

= 2(5a - 8a^2 -16ab + 8a^2)

= 2(5a - 16ab)

= 10a - 32ab

= 2(5a - 8a^2 -16ab + 8a^2)

= 2(5a - 16ab)

= 10a - 32ab

Added 6/6/2014 2:27:04 AM

This answer has been confirmed as correct and helpful.

4 - 1/3x = 1/9x

4 = 1/9x + 1/3x

4 = 4/9x

4x = 4(9) = 36

x = 36/4

x = 9

4 = 1/9x + 1/3x

4 = 4/9x

4x = 4(9) = 36

x = 36/4

x = 9

Added 6/6/2014 2:28:22 AM

This answer has been confirmed as correct and helpful.

6(5a - b) -5 (6b - 6a)

Question

Updated 5/3/2014 6:00:43 PM

2 Answers/Comments

6(5a - b) -5 (6b - 6a);

30a - 6b - 30b + 30a

= 60a - 36b

30a - 6b - 30b + 30a

= 60a - 36b

Added 5/3/2014 5:59:36 PM

This answer has been confirmed as correct and helpful.

-7+5x<-11x+21;

5x + 11x < 21 + 7;

16x < 28;

x < 28/16;

x < 7/4

5x + 11x < 21 + 7;

16x < 28;

x < 28/16;

x < 7/4

Added 5/3/2014 6:00:43 PM

This answer has been confirmed as correct and helpful.

(-a - 3b + 2)6ab **Weegy:** (-a - 2b + 4)6ab = -6a^2b - 12ab^2 + 24ab **User:** -1(-3)(-1)(3) **Weegy:** The answer is 5 5/21 (More)

Question

Updated 5/19/2014 11:29:38 PM

2 Answers/Comments

(-a - 3b + 2)6ab = -6a^2b - 18ab^2 + 12ab

Added 5/19/2014 11:29:20 PM

This answer has been confirmed as correct and helpful.

Confirmed by alfred123 [5/19/2014 11:35:50 PM]

38,674,801

questions answered

There are no comments.